2020
DOI: 10.23970/ahrqepccer240
|View full text |Cite
|
Sign up to set email alerts
|

Treatments for Acute Pain: A Systematic Review

Abstract: Objectives. To evaluate the effectiveness and comparative effectiveness of opioid, nonopioid pharmacologic, and nonpharmacologic therapy in patients with specific types of acute pain, including effects on pain, function, quality of life, adverse events, and long-term use of opioids. Data sources. Electronic databases (Ovid® MEDLINE®, PsycINFO®, Embase®, the Cochrane Central Register of Controlled Trials, and the Cochrane Database of Systematic Reviews) to August 2020, reference lists, and a Federal Register n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
31
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(55 citation statements)
references
References 49 publications
0
31
0
2
Order By: Relevance
“…The authors also stated that there might be a sufficient effect by NSAID or α-agonists monotherapy, as well as through nerve blocks [ 15 ], however, further studies assessing non-opioid use for pain control after otologic surgery is needed. Similar or even superior pain control of NSAIDs compared to opioids such as hydrocodone have been shown for various other surgical procedures such as rhinoplasties [ 16 ] or for acute pain in general, including postoperative pain [ 17 ].…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…The authors also stated that there might be a sufficient effect by NSAID or α-agonists monotherapy, as well as through nerve blocks [ 15 ], however, further studies assessing non-opioid use for pain control after otologic surgery is needed. Similar or even superior pain control of NSAIDs compared to opioids such as hydrocodone have been shown for various other surgical procedures such as rhinoplasties [ 16 ] or for acute pain in general, including postoperative pain [ 17 ].…”
Section: Discussionmentioning
confidence: 85%
“…Nevertheless, we believe that this questionnaire based analysis provides important aspects and insights to possibilities of non-opioid therapy for postoperative pain. As mentioned above, in several other surgical fields sufficient postoperative pain control with NSAIDs comparable or even superior to opioids has been shown in randomized studies and meta-analyses [ 16 , 17 , 24 , 25 ]. Primarily, treatment of pain following otologic surgery should therefore be attempted without opioids.…”
Section: Discussionmentioning
confidence: 99%
“…A substantiative body of research has evaluated the potential for multimodal chiropractic care to reduce or manage musculoskeletal pain. Recent systematic reviews and meta-analyses have concluded that SM as a part of multimodal chiropractic care has favorable outcomes on pain severity in patients with chronic LBP [82,83] and acute LBP with radiculopathy [84]. Additional reviews also support that SM can be a beneficial component of treatment plans for reducing the severity of both neck [85,86] and LBP [87,88].…”
Section: Painmentioning
confidence: 99%
“…Com o propósito de modular a dor e aumentar a amplitude de movimento, segundo a Academia de Terapia Manual Americana publicada pela IFOMPT (Federação Internacional de Fisioterapeutas Ortopédicos Manipulativos)². Dor é uma experiência sensitiva e emocional desagradável associada, ou semelhante àquela associada, a uma lesão tecidual real ou potencial 3 . A dor é quase universal, contribuindo substancialmente para a morbidade, mortalidade, incapacidade e sobrecarga do sistema de saúde 4 .…”
unclassified